(untitled) (Bangladesh Journal of Pharmacology, 2015)
In vitro and in vivo studies were undertaken to evaluate the pharmacologically mechanistic background to validate the traditional uses of Rumex acetosa in the treatment of emesis and gastrointestinal motility disorders such as constipation and diarrhea. In rabbit jejunum preparation, methanolic extract of R. acetosa (0.01-1.0 mg/mL) caused a transient spasmogenic effect, followed by the spasmolytic effect (3-10 mg/mL). In presence of atropine, spasmogenic effect was blocked while spasmolytic effect was emerged, suggesting that spasmogenic effect was mediated through activation of muscarinic receptors. Extract inhibited the K+ (80 mM)-induced contraction, suggesting Ca2+-cha-nnel blockade, which was further confirmed when pretreatment of tissue with extract shifted the Ca2+ concentration-response curves to the right, similarly as verapamil. R. acetosa also exhibited the significant antiemetic activity (p<0.05) against different emetogenic stimuli, when compared with chlorpromazine. This study confirms the presence of gut modulator (spasmogenic and spasmolytic) and antiemetic activates, validating its traditional uses.